THE ROLE OF VARIOUS METHODS OF KIDNEY DRAINAGE IN OBSTRUCTIVE PYELONEPHRITIS - Ivashchenko, D.M.; Dudchenko, M.O.; Kravtsiv, M.I.; Prykhidko, R.A.; Shevchuk, M.P.; Shchasnyi, D.M. (World of Medicine and Biology, 2021)
The study is devoted to the analysis of methods for drainage of the renal pelvis in the presence of a symptom complex of acute purulent obstructive pyelonephritis, comparison of various drainage methods (internal and external), analysis of the severity of inflammatory changes in the blood and urine, dynamics of laboratory parameters. In two groups of patients, the corresponding indicators were analyzed when performing internal (stenting) and external (nephrostomy) drainage of the urinary tract. According to the results, a more rapid decrease in blood and urine leukocytosis in the external drainage group was noted, the hyperthermic reaction of the body was also reduced faster, and there were more positive changes in the ultrasound picture. According to the results of the study, we can say that both methods of drainage are indicated in the presence of obstructive pyelonephritis as one of the components of treatment, and the method of external drainage is more effective than internal stenting.
Keywords: urethral stent; pyelonephritis; inflammation; infection; nephrostomy